Biomechanical evaluation of novel intra- and extramedullary assembly fixation for proximal humerus fractures in the elderly - Zhu, Zhengguo; Chang, Zuhao; Zhang, Wei; Qi, Hongzhe; Guo, Hao; Li, JiaQi; Qi, Lin; Nie, Shaobo; Tang, Peifu; Liang, Yonghui; Wei, Xing; Chen, Hua (Frontiers in Bioengineering and Biotechnology, 2023)
A novel intra-and extra-medullary assembly fixation was introduced and achieved good clinical results in complex proximal humeral fractures, but evidence of its comparability with traditional fixation is lacking. This biomechanical study aimed to compare it with traditional fixation devices in osteoporotic proximal humeral fracture.Methods: Three-part proximal humeral fractures with osteopenia were created on 12 pairs of fresh-frozen humeri specimens and allocated to three groups: (1) lateral locking plate, (2) intramedullary nail, (3) intra-and extra-medullary assembly fixation.Specimens were loaded to simulate the force at 25° abduction. Thereafter, an axial stiffness test and a compound cyclic load to failure test were applied. Structural stiffness, number of cycles loaded to failure and relative displacement values at predetermined measurement points were recorded using a testing machine and a synchronized 3D video tracking system.In terms of initial stiffness, and number of cycles loaded to failure, the intraand extra-medullary assembly fixation group showed obvious improvement compared to other groups(P＜0.017). The mean relative displacement value of measurement points in intra-and extra-medullary assembly fixation group was smaller than that in other 2 groups. But there was no significant difference until 10000 cycles. The mean relative displacement of the intramedullary nail group (3.136 mm) exceeded 3 mm at 7500 cycles of loading.In this test model, axial fixation can provide better mechanical stability than non-axial fixation. The intra-and extra-medullary assembly fixation is better able to prevent varus collapse for elderly proximal humeral fractures with posteromedial comminution.